HUBUNGAN ANTARA PRESTASI MAHASISWA DAN KEMAMPUAN BERBAHASA INGGRIS DENGAN LAMA STUDI (Studi Kasus pada Wisudawan Universitas Merdeka Pasuruan Tahun Ajaran 2016/2017) - Dwita Laksmita Rachmawati; Vita Fibriyani (Universitas Bumigora, 2018)
Education is the most important thing in a person’s life. Formal education is the learning process held by a particular educational institution, starting from the elementary, secondary, and higher education. To produce well-qualified college graduates, good teaching and learning process is needed. Determination of learning achievement in Higher Education is in the form of score of test results and observation conducted by the lecturer. The competence of college graduates cannot be seen only from the GPA and study duration, but also the ability of foreign language such as English. This study aims to determine the relationship between student achievement and English proficiency with study duration. Sampling techniques is done randomly. Statistical analysis used for this study was Pearson correlation analysis and testing the hypothesis by using Z-test. The result of the analysis indicates that there is a significant relationship statistically between student achievement and graduates’ study duration of Merdeka University Pasuruan that is the correlation coefficient obtained was –0.515. It means that the better (higher) of students’ achievement the faster the length of study will be, and the lower the students’ achievement then the longer the duration of the study period will be. For the relationship between the students’ abilities of foreign language with the duration of study, obtained correlation coefficient of 0.102, but the relationship formed insignificant statistically.